2014
DOI: 10.1007/s40257-014-0106-4
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Age and Gender in Knowledge, Behaviors and Attitudes Towards Sun Protection: A Cross-Sectional Survey of Australian Outpatient Clinic Attendees

Abstract: This study highlights a number of gender- and age-specific findings with regards to sun protection. There are knowledge, attitude, and behavior deficiencies within each demographic group that need to be specifically targeted through educational and public health efforts in order to improve general sun protection measures and decrease the incidence of skin cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
25
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 17 publications
5
25
2
1
Order By: Relevance
“…1 Further, the rates of MCC were higher in men than in women and the age of diagnosis tends to be >65 years of age. In Australia, this difference in incidence between genders could represent differences in sun‐protective measures between these groups …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Further, the rates of MCC were higher in men than in women and the age of diagnosis tends to be >65 years of age. In Australia, this difference in incidence between genders could represent differences in sun‐protective measures between these groups …”
Section: Discussionmentioning
confidence: 99%
“…In Australia, this difference in incidence between genders could represent differences in sun-protective measures between these groups. 14 The increase in incidence over time could however, be attributed to improved cancer registration of patients with MCC and improved histopathological diagnosis with the use of immunohistochemistry. Another possible cause for the increasing global incidence of MCC could be the greater number of individuals being treated with immunosuppression for organ transplants, inflammatory diseases or human immunodeficiency virus.…”
Section: Discussionmentioning
confidence: 99%
“…Decreasing unprotected ultraviolet exposure is effective in preventing skin cancer [ 3 ]; thus, wearing sunscreen and wearing sun protective clothing are common recommendations for sun protection [ 4 ]. However, knowledge, behaviors, and attitudes regarding sun protection vary among the general population [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sociodemographic risk factors for reduced practice of sun protection include younger age, male gender, non-Hispanic white, Hispanic ethnicity, and low education level [ 5 , 15 , 16 ]. While previous studies have focused on some of the sociodemographically high risk groups, few studies examined sun protection behaviors among low-income primary care patients.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the use of SPPs were found to be significantly higher in those who had a higher level of education, younger age, in women and singles, in those with higher economic level, those living in cities, and those with a higher level of knowledge on the harmful effects of sunlight and the ways of protection. It has been reported in similar studies that the rate of using SPPs significantly increases in those with higher levels of education and monthly income and in women 8,[14][15][16][17] . The results of a survey by Yurtseven et al 17 administered to the students in vocational schools of health showed that use of SPPs was higher in female students.…”
mentioning
confidence: 99%